The Adaptation of Global Norms The 1951 Refugee Convention in Indonesia - Qatrunnada Daysa Fitri; Dwi Ardhanariswari Sundrijo (Eduvest - Journal of Universal Studies, 2024)
This article aims to explain and answer the research question: Why did the localization of the global norms of the 1951 Refugee Convention in Indonesia lead to the issuance of Presidential Regulation No. 125 of 2016? Indonesia has been a transit area for refugees since 1979 and is the third country in ASEAN with the highest number of refugees. However, Indonesia has never formally and officially adopted the 1951 Refugee Convention. To answer the research question, this study applies the concept of norm localization proposed by Acharya (2004) as the framework for the analysis. This concept explains that the localization process of global norms might lead to three possible outcomes: acceptance of the norms, adaptation and modification of the norms, or complete rejection of the norms. The adaptation of the global norms is the result of adjusting some elements of the norm that are considered more appropriate to the local situations. In this article, we argue that the consideration of humanitarian values, national interests, and domestic challenges are the three most significant domestic factors that influence the process of norm localization in Indonesia. This article discusses how the three factors influenced the process of policy/decision-making on how Indonesia should deal with its refugee issues. In conclusion, we mainly argue that Presidential Regulation No. 125 of 2016 is the result of a complex adaptation process of the UN 1951 Refugee Convention, which involved multidimensional issues, as well as a multi-actor that represents various interests.